Integrated Trinity Test With RPA-CRISPR/Cas12a-Fluorescence for Real-Time Detection of Respiratory Syncytial Virus A or B - Gong, Ling; Wang, Xiaowen; Li, Zhu; Huang, Guichuan; Zhang, Wei; Nie, Jin; Wu, Chunyan; Liu, Daishun (Frontiers in Microbiology, 2022)
Respiratory syncytial virus (RSV) is a common virus that causes respiratory infection, especially severe respiratory infection in infants and young children, the elderly people over 65 years old, and people with weak immunity. Currently, RSV infection has no effective vaccine and antiviral treatment. The number of deaths due to RSV infection is increasing every year. Moreover, RSV A infection occurs in large number and has severe clinical symptoms and complications than RSV B infection. Therefore, the development of a simple, rapid, inexpensive detection method with high amplification efficiency, high sensitivity, and specificity is very important for the diagnosis of RSV A or RSV B infection, which can help in the early clinical medication and prevent the progress of the disease. Therefore, we developed an integrated trinity test with an RPA-CRISPR / Cas12a - Fluorescence (termed IT-RAISE) assay system to detect RSV A or RSV B. The characteristic of the IT-RAISE assay system is that after target recognition, the reporter ssDNA is cleaved by Cas12a that is activated by different crRNA to detect the generated fluorescent signal. This method is simple and helps in adding all reagents rapid rapidly. It is a highly sensitive method that can detect 1.38×101 copies/μL of the target sequences, and it can distinguish RSV A or RSV B infection within 37 min. In addition, clinical specimens were detected for IT-RAISE assay system. It was found that the sensitivity and specificity of RSV A were 82.61% and 90%, respectively; and those of RSV B were 75% and 93.33%, respectively. The cost of a specimen for IT-RAISE assay system was RMB 15.46 yuan. IT-RAISE assay system has good clinical application prospect for detecting RSV A or RSV B infection; it is a simple, rapid, inexpensive method with high amplification efficiency, high sensitivity, and high specificity. The IT-RAISE assay system might also detect other viral or bacterial infections.